Home or hospital as the place of end-of-life care and death: A survey among Chinese residents of Macao - Tam, Kuai In; Che, Sok Leng; Zhu, Mingxia; Leong, Sok Man (Frontiers in Public Health, 2023)
Objectives The study was the first to explore Chinese residents’ preferred place of care at the end-of-life, and preferred place of death in Macao. Methods A cross-sectional questionnaire survey was conducted online and face-to-face. The questionnaire was designed in Chinese, and both online and face-to-face survey were conducted in Chinese. The study was set in Macao. Macao residents aged 18 and above were recruited. Results A total of 737 responses were valid. 65% were female, aged between 19 – 101; 43.4% of respondents preferred to be cared for at home in the last 6 months, however, less than one-fifth preferred to die at home. A third of respondents chose to die in the hospice, and over a quarter of them preferred to die in hospitals. Compared with people aged between 18 - 39, people aged between 40 - 64 did not want to be cared for at home in the last 6 months, and they did not want to die at home either. Conclusions Results of the study suggested that there is a need for palliative home care in Macao, the government should consider developing such service, and review current laws and regulations in supporting the service. Education is equally important for healthcare professionals, enabling them to support palliative care development in the community.